Predlog izdelave korpusa humorja v govoru za slovenščino: Mira Krajnc Ivič, Špela Antloga (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Spoken Slovene Corpus of Humor: A Draft Proposal. The first part of the paper presents the theories of humor (Superiority Theory, Release Theory, and Incongruity Theory), and as their neutral integration and complementation, Raskin's Semantic Theory of Humor, as well as its extension, Attard's General Theory of Verbal Humor developed for analysing jokes. However, humor in conversation also arises spontaneously and depends more on the immediate context. Therefore, we also present a brief theoretical background of conversational humor. According to the Superiority Theory, humor is limited by national boundaries and time; it depends on loyalty to a group and identification with it. Research on conversational humour in the Slovene language is therefore essential. This could be accelerated by developing a suitable corpus. The second part of the article examines corpora of humor, namely: which languages have available spoken, written or multimodal corpora characterized as humorous; their size, material they cover, accessibility,annotation procedure of humorous segments, and which linguistic phenomena and other non-linguistic instruments were annotated. In conclusion, we present the survey results to help us evaluate whether the method used can be effective for determining the humor passages and deciding about the linguistic or non-linguistic means that affect the humorousness of the utterance or passage.